2022
DOI: 10.1002/btpr.3233
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fouling and breakthrough of process related impurities during depth filtration using confocal microscopy

Abstract: Titer improvement has driven process intensification in mAb manufacture. However, this has come with the drawback of high cell densities and associated process related impurities such as cell debris, host cell protein (HCP), and DNA. This affects the capacity of depth filters and can lead to carryover of impurities to protein A chromatography leading to early resin fouling. New depth filter materials provide the opportunity to remove more process related impurities at this early stage in the process. Hence, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…The charge properties of the a-LC dimer were not evaluated here due to its unknown structure. With very similar pI, the BsAb1 product was strongly positive (+11.4) compared with the homodimer (+2.9) and the a-LC (+1.3) at the pH (7.2) of the CCF; however it only led to limited adsorption of the BsAb1 product on the negatively charged elements of the X0HC filter media [ 21 ] at the relatively high salt concentration. Therefore, electrostatic interactions likely played very little role in retaining the a-LC variant due to its negligible positive charge.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The charge properties of the a-LC dimer were not evaluated here due to its unknown structure. With very similar pI, the BsAb1 product was strongly positive (+11.4) compared with the homodimer (+2.9) and the a-LC (+1.3) at the pH (7.2) of the CCF; however it only led to limited adsorption of the BsAb1 product on the negatively charged elements of the X0HC filter media [ 21 ] at the relatively high salt concentration. Therefore, electrostatic interactions likely played very little role in retaining the a-LC variant due to its negligible positive charge.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of the Millistak+® D0HC and X0HC filters have been recently investigated using confocal microscopy [ 21 ]. It was shown that the X0HC filter is composed of two layers both containing mainly naturally derived diatomaceous earth (DE) filter aids and a small portion of cellulosic fibers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The X0SP also showed improved HCP removal for several CHO‐derived antibodies. Parau et al (2022) found higher throughput during initial clarification of CHO cell culture fluid using the X0SP, with the X0SP and X0HC showing similar DNA breakthrough. Confocal microscopy was used to identify the location of foulants within the depth filters, with the greater capacity of the X0SP arising from better utilization of the second layer of the X0SP media.…”
Section: Introductionmentioning
confidence: 99%